(3CKQ GdGSJYOGOGJ GdhQGKjI Ydi GdYhGed GdhQGKjI GdLjfjI Ydi GdYhGed GdHFjI aj GYOGO aQb GdfNHI GdQjGVjI GdJfGaSjI QajYI GdeSJhi s - (3Hf YRjR , MfGfs; (3Hf Ycj, eMeO Bcdjs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2024)
(3fSYi ef NdGd gPG GdHMK GdYdej Edi JSdjW GdVhA HTcd Ydej fSHjG Ydi hGbY CcGOjejGJ cQI GdbOe GdLRGFQjI ef MjK eOi CgejI YedjI GdaMU hGdJTNjU GdeHqcQ Yf GdGSJYOGOGJ GdhQGKjI GdLjfjI aj TcdgG GdNGe, hGdJj jecf Cf fYJHQgG cfbWI HOGjI egeI fMh YedjI GdGSJKeGQ aj GdYhGed GdHjFjI GdecJSHI HGYJHGQgG GdeJZjQ GdJGHY GdeSGYO Ydi EHQGR GdGSJYOGOGJ GdhQGKjI GdLjfjI, hgPG df jJe EdqGef NdGd YedjI Jcqjja GdWQjbI GdJQHhjI GdHjOGZhLjI,hcPG MJi HGdfSHI dYedjI Jcjqja GdefTBJ hGdhSGFd GdHjOGZhLjI hJhajQ Ld GdEecGfjGJ GdeGOjI hGdJcfhdhLjI GdeJWhQI GdJj JSGge aj EYOGO GdfNHI GdQjGVjI GdeMdjI GdeSJbHdjI aj cQI GdbOe GdLRGFQjI, dgPG befG HELQGA HMK Ydej YjfI JQGhMJ Edi (B97 (3ef Hjfge eOQH QjGVj heQHj QjGVj heSJTGQ QjGVj Ydi eSJhi GdCcGOjejGJ hGdfhGOj GdcQhjI GdLRGFQjI, hbO GSJNOefG GdefgL GdhUaj GdJMdjdj dJbOje JTNjU dcTa eLQjGJ YedjI aMU hJTNjU GdGSJYOGOGJ GdhQGKjI GdLjfjI ef LejY LhGfH GdTNUjI GddGYH GdQjGVj, ceG GYJeOfG aj LeY HjGfGJ ehVhY GdOQGSI Ydi WQjbI GdGSJHjGf, ceG befG HELQGA ebGHdI fUa ehLgI eY GdeOQHjf GdQjGVjjf hGdeSJTGQjf GdQjGVjjf(B.s
(3OcJhQGIs
Keywords: (3GdEQTGO GdfaSj G dQjGVjs